The Relationship between the “Dark Triad” Personality Traits and Deviant Behavior on Social Networking Sites - Ellis, Timothy J. (2017)
Many aspects of the Internet have been described as taking a “dark turn”, as incidents of spear-phishing, identity theft, and other known cyber threats are becoming more commonplace. Social networking sites (SNSs) such as Twitter, Facebook, Instagram, Snapchat, and other services with user-generated content (UGC), provide a platform to facilitate these types of behavior. While these SNSs encourage respectful or acceptable behavior and adherence to conduct standards, incidences of obscene language, personal attacks, cyberbullying, racial, gender or sexual bias, and hate speech are rampant. Prior research suggests that this type of unacceptable or deviant behavior can be attributed to Dark Triad personality traits (i.e., narcissism, Machiavellianism, and psychopathy). Using the lens of the Dark Triad and an extensive literature review, a Short Dark Triad (SD3) survey study was conducted to investigate the gap in Information Systems (IS) research and the influence of deviant behaviors and its acceptance in SNSs